Clinical characterization of common pathogenic variants of SOD1-ALS in Germany - Wiesenfarth, Maximilian; Forouhideh-Wiesenfarth, Yalda; Elmas, Zeynep; Parlak, Özlem; Weiland, Ulrike; Herrmann, Christine; Schuster, Joachim; Freischmidt, Axel; Müller, Kathrin; Siebert, Reiner; Günther, Kornelia; Fröhlich, Elke; et al. (Journal of Neurology, 2024)
Pathogenic variants in the Cu/Zn superoxide dismutase (SOD1) gene can be detected in approximately 2% of sporadic and 11% of familial amyotrophic lateral sclerosis (ALS) patients in Europe. We analyzed the clinical phenotypes of 83 SOD1-ALS patients focusing on patients carrying the most frequent (likely) pathogenic variants (R116G, D91A, L145F) in Germany. Moreover, we describe the effect of tofersen treatment on ten patients carrying these variants. R116G patients showed the most aggressive course of disease with a median survival of 22.0 months compared to 198.0 months in D91A and 87.0 months in L145F patients (HR 7.71, 95% CI 2.89–20.58 vs. D91A; p < 0.001 and HR 4.25, 95% CI 1.55–11.67 vs. L145F; p = 0.02). Moreover, R116G patients had the fastest median ALSFRS-R progression rate with 0.12 (IQR 0.07–0.20) points lost per month. Median diagnostic delay was 10.0 months (IQR 5.5–11.5) and therefore shorter compared to 57.5 months (IQR 14.0–83.0) in D91A (p < 0.001) and 21.5 months (IQR 5.8–38.8) in L145F (p = 0.21) carriers. As opposed to D91A carriers (50.0%), 96.2% of R116G (p < 0.001) and 100.0% of L145F (p = 0.04) patients reported a positive family history. During tofersen treatment, all patients showed a reduction of neurofilament light chain (NfL) serum levels, independent of the SOD1 variant. Patients with SOD1-ALS carrying R116G, D91A, or L145F variants show commonalities, but also differences in their clinical phenotype, including a faster progression rate with shorter survival in R116G, and a comparatively benign disease course in D91A carriers.
CRIS-Team Scopus Importer:2024-08-23
Keywords: Amyotrophic lateral sclerosis; Clinical phenotype; Motor neuron disease; SOD1; Tofersen